Antioxidant Potential and Total Phenolic Content of Essential Oil and Various Extracts from Alpinia malaccensis (Burm.f.) Roscoe - Sethi, Sonali; Prakash, Om; Pant, A.K. (Asian Journal of Chemistry, 2015)
The aim of the present study was to evaluate antioxidant assays of essential oil and different extracts from Alpinia malaccensis (Zingiberaceae) rhizomes. The essential oil was found to possess higher phenolic contents (50.30 μg/mL) than the extracts. The antioxidant assay of essential oil and extracts evaluated by different methods revealed good to moderate antioxidant potential with different IC50 values viz. (160.62-230.34 μg/mL) in Fe3+ reducing power, (97.68-242.70 μg/mL) in Fe2+ metal chelating ability, (66.40-151.25 μg/mL) in DPPH, (61.81-136.16 μg/mL) in OH radical, (68.68-133.46 μg/mL) in NO radical and (58.33-199.87 μg/mL) in superoxide anion scavenging activities respectively in comparison to the standard antioxidants, butylated hydroxyl toluene, catechin, gallic acid and ascorbic acid. Based on these observations it can be concluded that this important herb can be a good source to develop a safe, ecofriendly and sustainable natural antioxidant and food preservative.